2011
DOI: 10.1074/jbc.m110.171454
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Protein Kinase D in Expression and Trafficking of ATP7B (Copper ATPase)

Abstract: ATP7B is a P-type

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
57
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 28 publications
2
57
0
Order By: Relevance
“…Previous studies showed that Ser-1121 in the flexible loop of the nucleotide binding domain was phosphorylated in response to copper (11,12); our mass spectroscopy analysis confirmed this finding. Because copper has been shown to alter interdomain interactions that may be functionally relevant for trafficking (35), we used site-directed mutagenesis to inactivate Ser-1121 as well as the closely associated site Ser-1116 located in the nucleotide (N) domain (13 S/TϾA/GϩN).…”
Section: Negative Charge Substitutions Of Eight Ser/thr In the C Termsupporting
confidence: 80%
See 2 more Smart Citations
“…Previous studies showed that Ser-1121 in the flexible loop of the nucleotide binding domain was phosphorylated in response to copper (11,12); our mass spectroscopy analysis confirmed this finding. Because copper has been shown to alter interdomain interactions that may be functionally relevant for trafficking (35), we used site-directed mutagenesis to inactivate Ser-1121 as well as the closely associated site Ser-1116 located in the nucleotide (N) domain (13 S/TϾA/GϩN).…”
Section: Negative Charge Substitutions Of Eight Ser/thr In the C Termsupporting
confidence: 80%
“…An ATP7B mutant with all four of these Ser changed to Ala exhibited defective TGN exit, suggesting that phosphorylation at these sites is required for TGN exit (12). The conformation of a different Ser cluster (Ser-340 and Ser-341), located in the loop between MBD3 and MBD4 also appears to be important for TGN exit in HEK293TRex cells (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We now find that even though a copper binding requirement for the E2 to the E1 transition is demonstrated by copper site mutations (33), experiments analogous to those with SERCA, in which Ca 2ϩ is first chelated with EGTA and then Ca 2ϩ is added to produce activation, cannot be easily done with ATP7A/B. In fact copper chelation with BCS produces inactivation due to removal of copper from the NMBD in addition to the TMBS, and very low phosphoenzyme formation is then obtained after the addition of copper and ATP.…”
mentioning
confidence: 99%
“…alkali labile) corresponds to aspartyl phosphate intermediate. Alkali labile phosphorylation of ATP7B does not occur after mutations at the transmembrane copper binding site (33) and is, therefore, linked specifically to enzyme activation (E2 to E1 transition) by occupancy of the cation transport site. It is noteworthy that ATP7A undergoes aspartate phosphorylation with kinetics analogous to ATP7B, but a lower level of protein kinase assisted phosphorylation (34).…”
mentioning
confidence: 99%